Clinical research progress of transanal opening of intersphincteric space in the treatment of anal fistula - Han Jing; Zheng Xueping (结直肠肛门外科)
Anal fistula is a common anorectal surgical disease, mostly caused by anal gland infection. Surgical intervention is currently the mainstream treatment for anal fistula, but balancing the protection of anal sphincter function and improving the cure rate remains a challenge in the development of anal fistula surgery. Transanal opening of the intersphincteric space (TROPIS) is one of the sphincter-preserving surgical procedures for the treatment of anal fistula. It fully protects the function of the anal sphincter with few complications, making it a minimally invasive surgical approach for the treatment of anal fistula that has received widespread attention. This article summarizes the relevant literature on the treatment of anal fistula with TROPIS in recent years. Based on the pathogenesis of anal fistula and the theoretical foundation of TROPIS, it comprehensively elaborates the research and clinical progress of TROPIS in the treatment of anal fistula in recent years, thereby further promoting the optimization and development of TROPIS.